7-year follow-up after open reduction and internal screw fixation in Bennett fractures - Leclère, Franck Marie Patrick; Unglaub, Frank (Archives of orthopaedic and trauma surgery, 2012)
Bennett fractures are unstable, and, with inadequate treatment, lead to osteoarthritis, weakness and loss of function of the first carpometacarpal joint. This study focuses on long-term functional and radiological outcomes after open reduction and internal fixation. Between June 1997 and December 2005, 24 patients with Bennett fractures were treated with open reduction and internal fixation with screws at our center. Radiological and functional assessments including range of motion of the thumb and pinch and grip strength were performed 4 months post-procedure and at the long-term follow-up, on average 83 months after surgery.
Gesehen am 20.07.2018